Anesthetic drug concentrations and placental transfer rate in fetus between term and preterm infants, twins, and singletons - Liu, Hao; Miao, Jing-Kun; Cai, Meng; Gan, Lin; Zhao, Hui-Qing; Lei, Xiao-Feng; Yu, Jin (Frontiers in Pharmacology, 2023)
Objective: This study aims to determine the drug concentration of etomidate, remifentanil and rocuronium bromide for general anesthesia in fetus and the placental transport rate between term and preterm delivery, twins and singleton. Study design: Sixty parturients with 72 fetuses undergoing cesarean section under general anesthesia were included. According to whether the fetus was a twin or premature, parturients were divided into Group I (Term singleton), Group II (Premature singleton), Group III (Term twins) and Group IV (Premature twins). The preoperative demographic characteristics and laboratory examination of parturients, hemodynamic indicators, the Apgar score of neonates at 1, 5, and 10 minutes after delivery and specific assigned values, umbilical artery blood gas analysis results, neonatal weight and resuscitative measures were recorded. Anesthetic drug concentrations in maternal arterial (MA), umbilical arterial (UA) and umbilical venous (UV) blood were detected by Ultra Performance Liquid Chromatography Tandem Mass Spectrometry (UPLC-MS/MS). Result: No significant differences were observed in the concentrations of etomidate, remifentanil and rocuronium bromide in MA, UV and UA blood as well as in the UV/MA and UA/UV ratios between term and preterm infants, twins and singletons. Moreover, there was no variation in the anesthetic drug concentration among each pair of twins. Additionally, no correlation was found between the neonatal weight and the plasma concentrations of anesthetic drugs in UV and UA blood except for remifentanil in UA blood. Conclusion: Preterm or twin deliveries do not affect the neonatal concentration of etomidate, remifentanil and rocuronium bromide used in general anesthesia for cesarean sections. (www.chictr.org.cn, registration number: ChiCTR2100046547).